Análise da distribuição espacial dos homicídios juvenis em um município brasileiro de tríplice fronteira no período de 2000 a 2007 - Andrade, Luciano de (2009)
The objective of this research was to analyze the mortality distribution spatial of homicides among youngsters from 15 to 24 years in the city of Foz do Iguaçu-PR, located in the triple frontier Brazil, Paraguay and Argentina. We carried out an ecological study, cross-sectional secondary data from 2000 to 2007, using a spatial data area. Data were obtained from the information system mortality (SIM) and supplemented with records from the Forensic Institute and the Integrated Services in the Emergency Trauma. Population, socioeconomic and demographic information were provided by the Brazilian Institute of Geography and Statistics (IBGE). The city was divided into 11 areas of population growth, where 873 deaths were spatially analyzed through programs ArcGIS® 9.2 and GeoDaTM, the global Moran index and local levels were used in order to assess the spatial autocorrelation between the rates of homicide and the socioeconomic and demographic indicators that characterize the different areas. We performed also an analysis to identify the spatial association for the area with the highest percentage of imports of homicides. The results showed a negative spatial autocorrelation (I = -0.3563, p = 0.0250), showing high murder rates in all AEDs, but dissimilar to each other, meaning that the EDA with a high rate of murder is surrounded by neighbors with "low" rate of homicide and vice versa, this shows that the problem of homicides in the city is not a local phenomenon but global, affecting all regions of the municipality. The AED 6 - Jardim América, had the highest homicide rate, because it is a region of high population mobility. It is the region of the Friendship Bridge, the main entry of products imported illegally from Paraguay. As for the AED with the highest percentage of of young homicide import, the one that mattered most was the AED 9 with about 60.00%, being also identified a spatial association (High-High cluster) among AEDs 6, 9 and 5. It is a region predominantly bordering with Paraguay, with great quantitative resident and floating population, marked by struggles, class conflicts and economic inequality. The socioeconomic indicators related to the degree of people occupation in formal and informal sectors showed spatial autocorrelation with statistic significance for the rates of young people homicide and AED importer. It follows that the distribution of juvenile homicides in the city is significantly influenced by the degree of occupation.